LEGAL PROTECTION OF EMPLOYEES DUE TO UNILATERAL TERMINATION OF EMPLOYMENT DUE TO FORCE MAJEURE COVID-19 PANDEMIC - Ayun Kencana R; Agus Budianto; Hosiana Gultom (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
The Covid-19 pandemic has brought a significant impact on various sectors, including the economy. Many companies suffered setbacks losses which led to layoffs for reasons of the Covid-19 pandemic which was categorized as a force majeure. However, the decision was actually detrimental to workers as it was not in accordance with the provisions of Law No.13 / 2003. Therefore, this study tries to examine the legal protection and legal consequences of termination of employment under the reasons of the Covid-19 pandemic force majeure. The aim of this study is to analyze and trace the legal protection of workers who have been unilaterally laid off during the Covid-19 pandemic and the legal consequences that arise from layoffs based on Law No. 13 of 2003 concerning Manpower. This study uses empirical normative legal research methods and uses secondary data consisting of primary, secondary and tertiary legal materials. This study is classified as a qualitative research, with the type of methodology used is an approach to legal systematics and an approach to legal cases. The data used in this analysis are secondary data obtained through literature study techniques and supported by primary data obtained by interview techniques. In view of Presidential Decree No. 12 of 2020, the results of the analysis show that the Covid-19 pandemic is regarded as a force majeure. Subject to the provisions of Law No. 13 of 2003, the legal protection for workers who are laid off due to force majeure is regulated in Article 164 paragraph (1) with the provisions in Article 156. It is necessary to note that when a layoff occurs due to law, employers are obliged to provide severance pay to workers. In this regard, in maintaining business continuity in the current situation, the government's efforts regarding the fulfillment of severance pay are contained in SE M / 3HK.04 / III / 2020, which fundamentally employers and workers can make a mutual agreement.